Perception of Agricultural Students and Agro-professionals towards Agricultural Education and Skill Development in India: Connect and Disconnect - Girijesh Singh Mahra , V.P. Sharma , V. Lenin , Satyapriya and Sujit Sarkar, (Indian Journal of Extension Education, 2015)
India is entering in phase of demographic dividend. Presently, India has more than 50 per cent of its population within theage group of 15 to 59 and 28 percent of population in age group of 15-29. Furthermore, by 2020, more than 65 percent ofIndian population will be under working age group. Manpower availability in agricultural sector indicated that more than12000 agricultural graduates pass out from the state agricultural universities (SAUs) all over the country every year, ofwhich only 2000 find job in private and public sector, leaving a huge number of graduates unemployed. This agriculturaldemographic dividend may become an asset as well as liability for Indian agriculture, depending upon the extent of skilldevelopment among agricultural students. For capturing perception of agricultural students, data has been gathered from100 agricultural students comprising from State Agricultural Universities, MANAGE and ICAR-IARI. To analyze theperception of agro-professionals, 25 Kisan Call Centre level- I graduate employees and 25 agro entrepreneur wereinterviewed. The present study has analyzed the existing perception of agricultural students and agro-professionalstowards agricultural education and skill development in India. Respondents have shown high importance level towardscore employability skills, professional skills and communication skills however respondents perceived that theimplementation level of core employability skills, professional skills and communication skills in Indian agriculturaleducation system is low. Skill gap analysis has shown that there is high skill gap in four core employability skills (teamwork, entrepreneurship, practical application and self-motivation), three professional skills (creativity, problem solvingability and statistical competence) and three communication skills (verbal communication, non-verbal communicationand technical writing) and these skills needs to be given more importance in agricultural education system in India.